Multidisciplinary Evaluation and Treatment of Necrotizing Fasciitis in a Type I Diabetic in a Community Military Hospital. Issue 2 (April 2021) - Bemis, Carl; Wendt, Erin D.; Patterson, Shane; Kluesner, Joseph; Tracy, Erin; Kelly, Jason; Antonio, Andrew
Abstract : A 38-year-old right-hand dominant male mechanic with uncontrolled diabetes mellitus type I presented to the emergency department (ED) complaining of worsening pain and swelling in his right hand. In the ED, a computed tomography scan confirmed the presence of soft-tissue edema in the right arm, but necrotizing fasciitis (NF) was not initially considered as a diagnosis. His Laboratory Risk Indicator for NF (LRINEC) score at the time of his hospitalization was 4, indicating a less than 50% chance of NF. Within 12 hours of admission, he developed increased violaceous, nonblanching skin of his dorsal fingers, increased swelling in his hand and forearm, bullae development in his palm and index finger, and a high fever. His LRINEC score had increased to 7, making NF up to 75% likely. He was urgently taken to the operating room (OR) for extensive debridement then admitted to the intermediate care unit for medical stabilization. He was subsequently taken back to the OR for serial debridements, and a negative pressure wound therapy device was placed once the wound was successfully debrided down to viable tissue. This is a case study of the multidisciplinary approach taken to the very ill patient at a community military hospital.